Herpes Simplex Epithelial Keratitis and Contact lens: A Case Report - Li, Ziqing (Canadian Journal of Optometry, 2024)
Herpes simplex virus keratitis is an ocular infection arising from the reactivation of HSV; if not promptly addressed, it can lead to diminished visual acuity and potential blindness in the affected eye. The sight-threatening aspects of this infection are primarily associated with the development of scarring and opacity. A 22-year-old woman, an otherwise healthy contact lens wearer, sought medical attention with complaints of painful, red, and photophobic eyes. Upon examination, a dendritic ulcer was observed on the right eye, accompanied by toxic keratopathy in both eyes. The treatment regimen that was implemented consisted of valacyclovir and ocular lubrication. The disruption of the host's natural immunological barriers, exacerbated by suboptimal contact lens handling, paved the way for subsequent dendritic ulceration. This occurrence was instigated by the reactivation of the herpes simplex virus, underscoring the critical importance of timely intervention.